1999
DOI: 10.1002/(sici)1097-4636(19991205)47:3<292::aid-jbm2>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Bilayered biodegradable poly(ethylene glycol)/poly(butylene terephthalate) copolymer (Polyactive?) as substrate for human fibroblasts and keratinocytes

Abstract: The purpose of this study was to find an optimal polymer matrix and to optimize the culture conditions for human keratinocytes and fibroblasts for the development of a human skin substitute. For this purpose porous, dense bilayers made of a block copolymer of poly(ethylene glycol terephthalate) (PEGT) and poly(butylene terephthalate) (PBT; Polyactivetrade mark) with a PEGT/PBT weight ratio of 55/45 and a PEG molecular weight (MW) of 300, 600, 1000, or 4000 Da were used. The best performance was achieved with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 23 publications
0
33
0
1
Order By: Relevance
“…The inherent instability of these hydrogels due to the high mobility of the PEG chains may have inhibited the spreading of cell types exhibiting high tensile stress (such as skeletal muscle cells and fibroblasts 28 ) or may have changed the surface characteristics (e.g., surface charge), parameters that could be important for skeletal muscle cell attachment and/or growth. 8 On the other hand, the high water content of the PEGT/PBT compositions with a higher wt % of PEG induced differentiation of chondrocytes due to their rounded morphology on these substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inherent instability of these hydrogels due to the high mobility of the PEG chains may have inhibited the spreading of cell types exhibiting high tensile stress (such as skeletal muscle cells and fibroblasts 28 ) or may have changed the surface characteristics (e.g., surface charge), parameters that could be important for skeletal muscle cell attachment and/or growth. 8 On the other hand, the high water content of the PEGT/PBT compositions with a higher wt % of PEG induced differentiation of chondrocytes due to their rounded morphology on these substrates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PEGT/PBT formulations with a PEGT content of 70 wt % have bone-bonding properties 1 while polymers with a PEGT content of 55 wt % are optimal as skin substitutes. 8,9 Engineered (soft or hard) tissues could form the basis for novel therapies for patients suffering from the loss of tissue or its function. 10 One approach to the development of functional tissues is the introduction of isolated cells onto biodegradable polymer scaffolds that provide a defined structure for cell attachment and tissue organization and mimic the key properties of the tissue to be engineered.…”
Section: Introductionmentioning
confidence: 99%
“…This composition supported the growth of fibroblasts and keratinocytes. 20 The scaffolds were circular, with a diameter of 5 mm and a thickness of 220 -260 m and a porosity of 70 -80%. Pore size was varied with the following diameters: group 1, 20 -75 m; group 2, 75-212 m, group 3, 250 -300 m. Scaffold morphology from both sides of the scaffold is shown in Figure 2 using standard SEM analysis.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Nevertheless, the bilayered epidermal-dermal construct has been rarely developed on nanofibrous membranes. For its creation, other forms of synthetic and natural polymers have been used, for example a knitted PLGA mesh combined with collagen-hyaluronic acid sponge [96], porous scaffolds made of a copolymer of poly(ethylene glycol terephthalate) and poly(butylene terephthalate) [97] matrices containing fibrin, collagen, hyaluronan and their combinations [98][99][100], and even spider silk woven on steel frames [101]. Thus, we have attempted to develop a bilayer of keratinocytes and skin fibroblasts using nanofibrous PLA membranes, fixed in adapted CellCrown inserts (Scaffdex, Tampere, Finland).…”
Section: Nanofibers In Skin Tissue Engineeringmentioning
confidence: 99%